Comparison and Analysis of Commonly Used Involute Spline Standard at Home and Abroad - Pei Bang; Liu Shujie; Li Yao; Fan Youhang (Jixie chuandong)
In the work practice,the different countries,different standard involute spline will be often encountered,such as the Chinese National Standard（ GB Standard）,the International Organization for Standardization（ ISO） standard,the Deutsch Industrial Norman（ DIN） standard,the American National Standards Institute（ ASNI） standard,the Japanese Industrial Standards（ JIS）,French standard（ NF） and the like. There are modular system,pitch system,dual pitch system,the pressure angle has 30°,37. 5°,45°,etc.,the definition method of accuracy class is different. The common used involute splines are introduced and contrasted,and the relationships between the different standards are analyzed,a reference for industrial application is provided.